Homogenization of diatom assemblages is driven by eutrophication in tropical reservoirs - Zorzal-Almeida, Stéfano; Bartozek, Elaine C. Rodrigues [UNESP]; Bicudo, Denise C. [UNESP] (Elsevier, 2021)
Eutrophication is one of the most widespread causes of biotic homogenization in freshwater ecosystems. Biotic homogenization can be characterized as reductions in local diversity (alpha) and occupation of available niches by more generalist species. Beta diversity is expected to decrease in more homogeneous communities, however, there is no consensus on how it responds to eutrophication. We used a space-for-time approach to analyze the process of biotic homogenization on diatom assemblages in response to eutrophication in tropical reservoirs ranging from oligotrophic to hypereutrophic conditions. Diatom assemblages were analyzed in phytoplankton and surface sediment from 12 reservoirs with different trophic levels. We calculated total beta diversity and turnover and nestedness components and used regressions to analyze their relationships with productivity differences (without distance effects). Total beta diversity had a positive influence of the trophic gradient, whereas turnover was not related to eutrophication. However, we found that eutrophication and lower species richness (alpha diversity) led to increasing rates of the nestedness component. We also observed that the homogenization process was not characterized by invasion of new species, but, on the contrary, by filtering nutrient-rich tolerant species also present in oligo-mesotrophic reservoirs and able to occupy available niches in the eutrophic reservoirs. These findings (increase in nestedness, decrease in alpha diversity, and development of tolerant species) suggest that biotic homogenization is leading to a simplification of diatom assemblages in tropical reservoirs, making assemblages from eutrophic and hypereutrophic reservoirs a subset of assemblages from oligotrophic and mesotrophic ones.
Keywords: Beta diversity; Biodiversity; Nestedness; Trophic gradient